Biostratigraphy and Paleoecology of FT-1 Well, Offshore Niger Delta, Nigeria: Implications for Paleoenvironment of Deposition - Agbaje P.O.; Ekinne O.A.; Olowa F.D. (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Although biostratigraphy and paleoecological studies are central to reconstructing paleodepositional environments and constraining source and reservoir rock distribution during petroleum exploration, detailed applications in offshore Niger Delta wells remain limited. This study analyzes the lithostratigraphy and foraminiferal assemblages of the FT-1 Well, offshore Niger Delta, over the 2,300–2,550 m interval to reconstruct the stratigraphic framework and paleoenvironmental history. Lithostratigraphic analysis reveals predominantly shaly facies, whereas foraminiferal biostratigraphy shows the dominance of benthic species (68.4%) over planktonic species (31.6%), a relationship that is diagnostic of outer–upper bathyal marine settings. The studied interval is assigned to the N18–N19 planktonic foraminiferal zones and to the NNDF 04–NNDF 06 benthic foraminiferal zones of the Neogene Niger Delta. The section is richly fossiliferous, containing abundant and diverse foraminiferal assemblages. The top of the N18–N19 interval is tentatively placed at 2,300 m based on the First Downhole Occurrence (FDO) of Globigerina nepenthes, while the base is constrained by the Last Downhole Occurrences (LDOs) of Neogloboquadrina dutertrei and Globorotalia tumida at 2,490 and 2,540 m, respectively. The NNDF 04 Zone extends from 2,300 to 2,430 m and is marked at its base by the occurrence of Cyclammina cf. minima; NNDF 05 spans 2,430–2,460 m, defined by the FDOs of C. cf. minima and Haplophragmoides narivaensis; NNDF 06 extends from 2,460 m to 2,550 m, the deepest analyzed sample, and is characterized by the continued occurrence of H. narivaensis. Paleoecological interpretation of the foraminiferal assemblages indicates mostly tropical–subtropical conditions with normal marine salinity, but includes cooler-water indicators such as Cyclammina cf. minima, Globocassidulina subglobosa, Uvigerina hispida, and Uvigerina auberiana, which are typical deep-water species. On the basis of the N18–N19 planktonic zonation, the sediments are interpreted to have been deposited during the Late Miocene–Early Pliocene. Collectively, these findings refine the stratigraphic framework and enhance understanding of the paleoenvironmental evolution of the Niger Delta’s offshore deposits, with implications for more accurate prediction of petroleum system elements.